2022
DOI: 10.55324/iss.v2i2.316
|View full text |Cite
|
Sign up to set email alerts
|

Numeracy Literacy Skills of Elementary School Students through Ethnomathematics-Based Problem Solving

Abstract: Background: Numeracy literacy is one of the aspects evaluated in the Minimum Competency Assessment (AKM), referring to the Programme for International Student Assessment (PISA) as a good practice for international level assessment. Aim: This study aims to analyze the numeracy literacy ability of elementary school students in ethnomathematics-based problem solving. Method: This research is a qualitative descriptive research with a case study method taking the subject of 28 grade IV students of SDN Lamper Kidul … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
11
0
2
Order By: Relevance
“…By incorporating ethnomathematics into mathematics learning videos and realistic mathematics education, students can be empowered in their learning activities and develop a deeper awareness of cultural relevance to their education (Yandani & Agustika, 2022). In addition, ethnomathematics-based problem-solving approaches have improved students' numeracy literacy skills and understanding of mathematical concepts (Iswara et al, 2022;Yuliana et al, 2022).…”
Section: S (Subject)mentioning
confidence: 99%
See 1 more Smart Citation
“…By incorporating ethnomathematics into mathematics learning videos and realistic mathematics education, students can be empowered in their learning activities and develop a deeper awareness of cultural relevance to their education (Yandani & Agustika, 2022). In addition, ethnomathematics-based problem-solving approaches have improved students' numeracy literacy skills and understanding of mathematical concepts (Iswara et al, 2022;Yuliana et al, 2022).…”
Section: S (Subject)mentioning
confidence: 99%
“…This illustrates that ethnomathematics is essential in connecting mathematical concepts with students' cultural backgrounds and everyday experiences. Ethnomathematics involves the study of mathematical concepts in local cultures, and their implementation in mathematics education has shown a positive impact on students' learning experience and mathematical understanding (Ergene et al, 2020;Hendriana & Buyung, 2020;Ida, 2023;Iswara et al, 2022;Bravo et al, 2023;Pathuddin et al, 2021;Prahmana et al, 2023;Virgana, 2019;Yuliana et al, 2022).…”
Section: S (Subject)mentioning
confidence: 99%
“…Lebih lanjut, studi terdahulu menambahkan bahwa model pembelajaran berbasis masalah yang dikolaborasikan dengan etnomatematika dapat membantu mengembangkan kemampuan literasi numerasi siswa (Iswara et al, 2022). Etnomatematika menyediakan pembelajaran yang dapat mendorong terciptanya motivasi tinggi untuk belajar numerasi.…”
Section: Bahan Ajar Yang Terbatas Untuk Menumbuhkan Kemampuan Literas...unclassified
“…To help recoup literacy losses, it has been suggested that more formal at-home literacy activities (e.g., focusing on printed words and letters, linking sounds, etc.) may help close the literacy gap of struggling readers compounded by COVID-19 (Iswara & Iswara, 2021). Although this is promising, it is unknown whether many parents have the necessary skills, knowledge, or time to assist children with these activities.…”
Section: Introductionmentioning
confidence: 99%